Gagasan Tentara, Kata-kata Media Nasional, ‘Kenyataan’ Massa Rakyat Indonesia - Budi Susanto (Antropologi Indonesia, 2004)
Regarding Indonesian recent extensive and intensive regional and communal violence, TNI, the Indonesian National Army-as one of the most responsible (and capable) state apparatus to deal with it-in fact, almost has not done something substantial. Or, violent actions in contemporary Indonesian (multicultural) societies, perhaps, have never been a legitimate monopoly of supposedly a modern state. Based on critical analysis of news and images disseminated by contemporary mass media in modern Indonesia, this paper tries to deconstruct a myth. It is a (anthropological) myth of presuming that thoughts (and identity), words (and language) and reality (and imagination) were different things; and that those three things were related one to another hierarchically. After the 'fall' of the New Order military regime in 1998, and even in its most chaotic period, since early year of 2000, TNI innocently and ironically has manipulated the myth in order to maintain its hegemonic (dual function) power in dealing with the Indonesian common people's expressions of looking for human rights and justice. Although, this paper likely does not believe any longer in the usual existing idea and practice of democracy that remains focus on making accountable the exercise of (military) government power. History of political economy has brought with it a fundamental change in the form of expanding business and financial power-modern audio-visual mass-media included. Cornering certain ironic contemporary typical Indonesian politico-economic and cultural representations, hopefully, this article would remind the readers on the allures and threats of a modernization which parades and sells out words, thoughts, and reality so recklessly.